Efeito protetor da quercetina sobre a toxicidade induzida pela oxitetraciclina em Rhamdia quelen - Pes, Tanise da Silva (2018)
The culture conditions in the fish culture can lead to stress situations, contributing to the occurrence of infectious diseases, considered a great challenge for the productive success of this activity. Thus, antibiotics have been used for therapeutic purposes and for prophylaxis, especially oxytetracycline (OTC), which has advantages in terms of efficacy and economy compared to other antibiotics. However, there is a great concern in the intensive use of antibiotics due to the development of antimicrobial resistance, besides the environmental problems caused by these drugs. The need for healthier foods has led to the demand for natural products. Quercetin incorporated into the diet may be a natural alternative to minimize the physiological changes caused by the use of antibiotics during cultivation, since its antioxidant activity has already been described, as well as anti-inflammatory, anticancer and antibacterial properties, among others. Thus, this work aimed to evaluate the possible protective effect of quercetin supplemented in the diet of silver catfish, as well as to verify if the compound reduces and/or minimizes the toxicity induced by the oral administration of OTC. In the first experiment, we aimed to test the effect of quercetin and to choose the best concentration for the fish. For this, the fish were divided into three groups and fed a control diet and diet containing two concentrations of quercetin (1.5 and 3.0 g per kg of diet) for a period of 21 days. The results indicated that quercetin did not promote any significant changes in hematological and biochemical parameters. Fish receiving diets containing quercetin showed decreased lipid peroxidation (LPO) (measured by lipid hydroperoxides (LOOH) and thiobarbituric acid reactive substances (TBARS) and increased activity of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione S-transferase (GST). In addition, levels of non-protein thiols (NPSH), total reactive antioxidant potential and ascorbic acid (AA) were higher in fish fed diets containing quercetin. There were no changes in cortisol levels and mRNA expression of growth hormone (GH), prolactin (PRL) and somatolactin (SL) in fish fed a diet containing quercetin when compared to control. In the second experiment, the fish were divided into four experimental groups and received the following experimental diets for 14 or 21 days: (i) - control, (ii)- 0.1 g OTC per kg of diet, (iii)- 1.5 g of quercetin per kg of diet; or (iv)- OTC+quercetin. We investigated the effect of quercetin on the stress and metabolism indicators, mRNA expression of GH, PRL, SL, corticotropin- releasing hormone (CRH), and two different proopiomelanocortins (POMCa and POMCb), as well as the analysis of OTC residue in fish muscles. By treating the oxidative indicators, the results showed that OTC induces an increase in the levels of LOOH, TBARS and carbonyl protein, decrease in the enzymatic activities of SOD, CAT, GST, GPx and NPSH and AA levels. Co-treatment with quercetin was able to prevent these effects on the muscle, brain, kidney and liver of the silver catfish. However, residual OTC values in fish muscle were below the limit of quantification. Finally, we can reinforce that OTC activates the stress response in silver catfish, due to the increase of plasma cortisol and a decrease of glucose levels at 14 and 21 days. In addition, it also altered the metabolic status of fish as it increased liver triglyceride levels as well as the liver activity of fructose-biphosphatase and glutamate dehydrogenase at 14 days. OTC treatment also stimulated Na+/K+-ATPase activity at 14 days and changed the expression of GH (at 14 and 21 days) and PRL (at 14 days). Thus, our study has proven that quercetin restores OTC damage by suggesting that the administration of quercetin may be a valuable strategy to prevent or attenuate antibiotic toxicity in different commercially important fish species.